A retórica como instrumento legitimador da prisão cautelar preventiva - Chediak, Jackson (2022)
This research is situated within the rhetoric studies, more specifically about forensic rhetoric and aims at figuring out the rhetoric as a legitimizing instrument of the precautionary arrest in two preventive decrees of Rondônia judiciary and one of national repercussions. The specific objectives established are: a) to identify arguments in preventive decrees as the basis for precautionary arrest; b) to verify persuasive elements related to the moral feeling of conformity of the audience in the decrees and c) to analyze how fear is inserted in the judge's arguments, to convince the jurisdictional ones of the decree legality. Thus, three documents have been analyzed from the perspective of rhetorical and argumentative studies: the advertising student’s preventive detention case; the professor’s case and the deputy’s arrest case. The method of investigation concerned documentary and bibliographic research with a qualitative approach. The analysis has been carried out based on rhetorical and argumentative studies, which made it possible to identify three general categories regarding argumentative strategies: fear; the authority figure; the linking or breaking processes. The similarities in the rhetorical strategies of the analyzed cases showed that the speaker's authority and the audience's passion determine what can be legitimized, in confrontation with the legal norm, regarding the hypotheses of appropriateness of preventive detention, from strategies based on fear as a central persuasive element. The rhetorical arguments found which can be related to fear were: a) punishment as an example for society; b) the media repercussion in the production of social insecurity; c) social commotion; d) imprisonment for the seriousness of the crime; and e) the fear of the accused's recidivism in the crime. Furthermore, the data point to strategies of authority and/or institutions used by the speaker (either represented by the judge - as a competent person, or by the defendant - considering the power he/she exerts over the victim - to lead the audience to an inadequate interpretation through rhetorical constructions to obtain adhesion and establish a consensus, between the rational and the passionate. Finally, the data show the argumentative strategies related to the processes of connection and dissociation, the first being associated with solidarity and the search for a union of interests and the second with the detachment between the person and his actions, so that the audience's point of view about the person is not led to the act